Electronic lexicography - Granger, Sylviane, 1951-; Paquot, Magali (Oxford : Oxford University Press, 2013)
Professional and academic lexicographers present and discuss innovations, ideas, and developments in all aspects of electronic lexicography including dictionary-writing systems and the integration of corpora for every kind of dictionary in every format.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Lexicography -- Data processing